Weight loss improves endothelial function independently of ADMA reduction in severe obesity - Rudofsky, Gottfried; Roeder, E.; Merle, T.; Hildebrand, M.; Nawroth, Peter Paul; Wolfrum, C. (Hormone and metabolic research, 2011)
This prospective study was performed in order to establish whether improvement of endothelial function after weight reduction can be explained by a decrease of elevated asymmetric dimethyl arginine (ADMA), an inhibitor of endogenous NO-synthase (eNOS). Therefore, 21 obese subjects (BMI: 41.1±6.4 kg/m2) were studied at baseline and after 12 weeks of weight reduction with a very low calorie diet. Biochemical and clinical parameters of endothelial function were assessed before and after weight loss. Biochemical parameters were determined by measurement of ADMA and soluble intercellular adhesion molecule (sICAM). Clinical parameters were assessed by pulse wave analysis (PWA). Weight intervention resulted in a 21.4±6.8 kg reduction of body weight from 119.7±12.8 kg at study start to 98.3±11.6 kg at study end (p<0.001). Accordingly, biochemical markers improved under weight reduction (ADMA from 0.47±0.07 mmol/l to 0.42±0.08 mmol/l; p=0.002; ICAM from 276±42 ng/ml to 236±29 ng/ml; p<0.001). Further, clinical parameters of functional endothelial function improved with an increase of deltaRI after salbutamol inhalation from −1% before to −9% after weight reduction (p=0.02). Interestingly, improvement of endothelial function correlated with improved HOMA index only (r=−0.60, p=0.04) but not with reduced ADMA levels, improved hypertension or reduced body weight. In conclusion, weight reduction with a very low calorie diet improves endothelial function measured by pulse wave velocity. The missing correlation with ADMA suggests possible further mechanisms underlying this observed effect, for example, improvement of insulin resistance.
Gesehen am 21.09.2022